Postoperative Pulmonary Edema after Total Knee Replacement for Rheumatoid Arthritis—A Case Report - KOBAYASHI, Seneki (Japanese Journal of Rheumatism and Joint Surgery, 1987)
A 60-year-old woman received total knee replacement (TKR) for right rheumatoid arthritic knee. Her operation past uneventfully under inhalation anesthesia, with a blood loss of 550 ml, and a 600 ml washed red blood cell (WRBC) transfusion. On the 2nd day after operation, 400 ml of WRBC were transfused for anemia. During the night of the 4th day, she showed paroxymal noctural dyspnea, and on the 5th day complained of nausea, vomiting, coughing, stridor, and palpitation. A moist rale was auscultated on the chest. Blood gas analysis showed severe hypoxemia. A chest radiograph showed a butterfly shadow and vanishing tumor. Pulmonary edema was evident. She was treated with oxygen inhalation, a diuretic, electrolytes, and human serum albumin. On the 8th day her general condition was improved and laboratory data became within normal range. In this case the postoperative pulmonary edema was likely to be due to increased permeability of pulmonary capillaries caused by operative invasion and decreased plasma osmotic pressure caused by massive WRBC and fluid transfusion. The general condition of a rheumatoid arthritic patient should be carefully controlled before, during and after a highly invasive operation such as total joint replacement.